A metallic furnace atomizer in hydride generation atomic absorption spectrometry: Determination of bismuth and selenium - Klassen, Aline (2008)
A flow injection hydride generation system with a metal furnace atomizer (Inconel 600® alloy) was employed for Bi and Se determination. The presented methods have linear ranges up to 200 and 500 μg L- 1 for Bi and Se, respectively, with good linearities (r2 = 0.9997 and 0.9974, respectively). The limits of quantification obtained according to IUPAC recommendations were 2.3 μg L- 1 for Bi and 6 μg L- 1 for Se, and the relative standard deviations (N = 6) based on Bi and Se analytical responses from real samples were 2.7% and 10%, respectively. Accuracy evaluations were based on certified materials such as SRM 361, SRM 363, and SRM 364 (steel alloys) for Bi, Mess-3 (marine sediment), SRM 397 (human hair), and Bio-Rad2 - 69042 (urine) for Se. Good agreements between the results were obtained at the 95% confidence level, according to the t-test.